Step
*
3
2
of Lemma
i-member-convex'
1. I : Interval
2. a : ℝ
3. b : ℝ
4. a ∈ I
5. b ∈ I
6. z : {z:ℝ| r0 < z} 
7. x : {z:ℝ| r0 ≤ z} 
8. y : {z:ℝ| r0 ≤ z} 
9. (x + y) = z
10. ((x/z) * a) + ((r1 - (x/z)) * b) ∈ I
11. (((x/z) * a) + ((r1 - (x/z)) * b)) = ((x * a) + (y * b)/z)
⊢ ((x * a) + (y * b)/z) ∈ I
BY
{ (RWO  "-1" (-2) THEN Auto) }
Latex:
Latex:
1.  I  :  Interval
2.  a  :  \mBbbR{}
3.  b  :  \mBbbR{}
4.  a  \mmember{}  I
5.  b  \mmember{}  I
6.  z  :  \{z:\mBbbR{}|  r0  <  z\} 
7.  x  :  \{z:\mBbbR{}|  r0  \mleq{}  z\} 
8.  y  :  \{z:\mBbbR{}|  r0  \mleq{}  z\} 
9.  (x  +  y)  =  z
10.  ((x/z)  *  a)  +  ((r1  -  (x/z))  *  b)  \mmember{}  I
11.  (((x/z)  *  a)  +  ((r1  -  (x/z))  *  b))  =  ((x  *  a)  +  (y  *  b)/z)
\mvdash{}  ((x  *  a)  +  (y  *  b)/z)  \mmember{}  I
By
Latex:
(RWO    "-1"  (-2)  THEN  Auto)
Home
Index